Cooperative learning strategies for effective speaking skills in health and nursing college students / Christine Kayan Ak Stephen Jussem - Stephen Jussem, Christine Kayan (2011)
Speaking is very important means for communicating, thinking, and learning. Fluency in speaking is essential component of learning as it enables students to learn concepts, develop vocabulary and perceive the structure of English language. Therefore, in order to have the ability to speak competently, one needs to learn oral language.